Letter - Butler, E. J.
1940-09-09 038-0039-002 Trades Council Committee of the Plymouth &. District Spanish Refugee Fund. 5 Alton Ter, North Hill Plymouth Sept - 9 - 1940 To the Secretary of The Trade Union Congress Dear Comrade, We have maintained in Plymouth for over 3½ years a hostel for forty Spanish children, the necessary funds being raised by the children themselves in concert work (£400 in this way), and by voluntary contributions and donations from individuals and organisations in Devon and Cornwall. Had the war not broken out we could have carried on our work without anxiety about finance but during recent months our supplies have been much depleted. We are therefore asking you to consider the possibility of giving Trade Union assistance. The present position is this. All the children who can be repatriated have returned to Spain and we are left with twelve children who must be maintained and provided for in England. Three of the boys and two of the girls have been apprenticed to trades in this town under Trade Union conditions and we have hopes of providing similar employment for the other children when they are of age.We are desirous of keeping the home going until the boys and girls can support themselves. If the Trades Unions of this country could each donate £1 per month we should be able to face our responsibilities with confidence.Will you please give the matter your earnest consideration. The work of carrying on the hostel is done by voluntary helpers and overhead charges are at a minimum. Yours fraternally E J Butler Hon.Secretary. P.S. My Committee wishes all national Bodies to make payments through you to me Thanking you in anticipation 292/946/38/39(II)